2007
DOI: 10.1073/pnas.0704679104
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal exposure to national flags affects political thought and behavior

Abstract: Political thought and behavior play an important role in our lives, from ethnic tensions in Europe, to the war in Iraq and the Middle Eastern conflict, to parliamentary and presidential elections. However, little is known about how the individual's political attitudes and decisions are shaped by subtle national cues that are so prevalent in our environment. We report a series of experiments that show that subliminal exposure to one's national flag influences political attitudes, intentions, and decisions, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 18 publications
4
102
2
3
Order By: Relevance
“…For example, Berger et al (2007) showed that Arizona voters were more likely to support a sales tax increase designed to fund education when they voted in schools, rather than other locations. As noted earlier, Hassin et al (2007) similarly found that people who strongly and weakly supported Israeli nationalism behaved more similarly when exposed to an Israeli flag.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 73%
“…For example, Berger et al (2007) showed that Arizona voters were more likely to support a sales tax increase designed to fund education when they voted in schools, rather than other locations. As noted earlier, Hassin et al (2007) similarly found that people who strongly and weakly supported Israeli nationalism behaved more similarly when exposed to an Israeli flag.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 73%
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, incidental exposure to environmental cues and irrelevant events has been suggested to shape political choices without participants' awareness (Bergeret al, 2007;Carteret al, 2011;Hassin et al, 2007;Healy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Important studies about flag influence on attitudes and political behavior come from Israel, a country where exhibition of national emblems is overwhelming. In a series of experiments Ran Hassin demonstrated that flags waving in the environment had appreciable effects although contact with them was ultra-short or unnoticed (Hassin et al, 2007(Hassin et al, , 2009). The first one was carried out with Israelis who, while taking a verbal task on a computer screen received flashes with pictures of the national flag with a duration so short (16 milliseconds), that they could not detect them.…”
Section: Flag Pressure and Intimidationmentioning
confidence: 99%